Nothern exposure. Season six - Frescho, Michael; Charleston, Jim; Morrow, Rob; Corbin, Barry, 1940-; Turner, Janine, 1963- (Universal City, CA : Universal Studios Home Entertainment, 2014)
After failing to read the fine print on his scholarship requirements, a young New Yorker is sent to the remote and eccentric town of Cicely, Alaska after he graduates medical school.
Dinner at seven thirty -- Eye of the beholder -- Shofar, so good -- The letter -- The robe -- Zarya -- Full upright position -- Up river -- Sons of the tundra -- Realpolitik -- The great mushroom -- Mi casa, su casa -- Horns -- The mommy's curse -- The quest -- Lucky people -- The graduate -- Little Italy -- Balls -- Buss stop -- Ursa minor -- Let's dance -- Tranquility rose.
Dolby digital 2.0 stereo, full screen 1.33:1.
Features: deleted scenes, featurette.
Rob Morrow, Barry Corbin, Janine Turner, John Cullum, Darren E. Burrows.
Originally broadcast on television 1994-1995.
TV rating: Not rated.
Closed-captioned.
Keywords: Physicians -- Alaska -- Drama; Television series; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs